Brain size growth in Australopithecus. Issue 130 (May 2019) - Cofran, Zachary
Abstract: Postnatal growth is one of the proximate means by which humans attain massive adult brain size. Humans are characterized by the maintenance of prenatal brain growth rates into the first postnatal year, as well as an overall extended period of growth. The evolution of this pattern is difficult to assess due to its relatively brief duration and the underrepresentation of well-preserved fossil individuals who died during this short period. In this study, I use Monte Carlo methods to reconstruct postnatal brain growth rates in Australopithecus afarensis and Australopithecus africanus, based on estimates of neonatal brain size and of likely brain size and age at death of infant specimens (A.L. 333-105, DIK-1-1, and Taung). Neonatal brain size is reconstructed from the empirical scaling relationship among catarrhines which humans follow, and conservative estimates of fossils' chronological ages and brain sizes are drawn from the literature. Simulated distributions of these values are used to calculate average annual rates (ARs) of brain growth and proportional size change from birth (PSC), which are compared to resampled statistics from humans, chimpanzees and gorillas of known age and sex. Simulated ARs and PSCs for A. afarensis are significantly lower than those of chimpanzees and gorillas. Both ARs and PSCs for A. africanus are similar to chimpanzee and gorilla values. These results indicate that although these early hominins were derived in some aspects of brain anatomy, high rates of brain growth did not appear until later in human evolution. Moreover, findings also imply that brain growth rates are not a simple function of adult brain size. This study provides important new information about the evolution of brain growth, despite limitations inherent in fossil samples.